Impacto da avaliação do desempenho na função pública local angolana: o caso particular de Luanda. Estudo expolatório - Brazinha, Manuel Firmino (2018)
The aim of this research is to find answers for better implementation of the Performance Evaluation System implemented in Angola (Decree No. 25/94 of July 1). This research has as general objectives: describe the performance evaluation process; evaluate the performance evaluation model of the Angolan civil service; introduce and develop an opinion on the results obtained. The methodology adopted was an analysis of the contribution of the lead authors on the subject from scientific papers  books, thesis and journals  making it possible to construct a questionnaire that resulted from this analysis and reflection of the authors consulted. The empirical work allowed collecting 109 questionnaires distributed in three provinces of Luanda district: Maianga, Samba and Belas. The results allow us suggesting solutions in order to improve the Performance Evaluation System implemented in Angola.